2022
DOI: 10.1039/d1gc04059f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deep eutectic solvents (DESs) and individual DES components on alcohol dehydrogenase catalysis: connecting experimental data and molecular dynamics simulations

Abstract: For a knowledge-based design of enzyme catalysis in deep eutectic solvents (DESs), the influence of the DESs properties (e.g., water activity, viscosity), and the impact of DESs and their individual...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 83 publications
0
37
0
Order By: Relevance
“…By shifting water content in DES toward higher values, the activity of the enzymes usually increases and at optimal conditions reaches higher values than those in reference systems. 67–70…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By shifting water content in DES toward higher values, the activity of the enzymes usually increases and at optimal conditions reaches higher values than those in reference systems. 67–70…”
Section: Resultsmentioning
confidence: 99%
“…In such DES the enzyme was highly active and stable, giving promising productivity. 68 To be more precise, a high HLADH half-life time peak was observed for ChCl:Gly at a water content of 40 vol% (higher than the half-life time observed in the aqueous buffer), which decreased at higher water contents. Even though we have shown that Ch:Gly at water content up to 35% is one of the least suitable DES for stabilisation of NAD coenzyme, these mixtures still showed improved coenzyme stabilisation ability compared to reference phosphate buffer commonly used for dehydrogenase-catalysed reactions, implying its potential as a storage medium.…”
Section: Future Perspectives For Enzymatic Catalysismentioning
confidence: 93%
See 1 more Smart Citation
“…[7] Recent developments showed great potential of using enzymes in low-water media, which became not limited to lipases. [8] When it comes to biorefineries, the possibility that enzymes can efficiently catalyze reactions in media containing different water proportions is clearly an asset, as it provides adaptation to varied (crude) effluent types.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐conventional media encompass a wide array of potential reaction systems, ranging from ionic liquids (ILs), deep eutectic solvents (DES), neat solvents, microaqueous reaction systems (MARS), and biphasic systems consisting of water and organic media [7] . Recent developments showed great potential of using enzymes in low‐water media, which became not limited to lipases [8] . When it comes to biorefineries, the possibility that enzymes can efficiently catalyze reactions in media containing different water proportions is clearly an asset, as it provides adaptation to varied (crude) effluent types.…”
Section: Introductionmentioning
confidence: 99%